Anxiety prevalence in lymphoma: A systematic review and meta-analysis - Vargas-Román, Keyla; Díaz-Rodríguez, C. Lourdes; Cañadas-de la Fuente, Guillermo Arturo; Gómez Urquiza, José Luis; Ariza, Tania; Fuente -Solana, Emilia I. de la (Health Psychology, 2020)
Objective: Hodgkin and non-Hodgkin lymphoma patients are at high risk of experiencing anxiety because the clinical processes and therapies they undergo produce strong adverse effects. In this review we discuss the prevalence of anxiety among these patients and examine the methods used for data collection, intervention frequency, types of instruments used to recognize anxiety, and data collection purposes, both in Hodgkin and non-Hodgkin lymphoma survivors and patients being treated or diagnosed with these diseases. Methods: This systematic review and meta-analysis of the literature was carried out using the following sources: PubMed, Scopus, LILACS, and PsycINFO. Results: The meta-analysis sample was n = 2,138 and the overall prevalence of anxiety was 19% (95% CI [12%, 25%]). According to the Egger test, there were no publication biases and no studies were eliminated after the sensitivity analysis. The I2 for the heterogeneity analysis was 92.6%. Conclusions: Hodgkin and non-Hodgkin lymphoma patients are vulnerable to suffering anxiety. It is important to focus on the psychological effect of anxiety during remission or current cancer treatments because they can affect patient outcomes.
Keywords: anxiety; cancer; hodgkin disease; lymphoma; non-hodgkin disease; Scopus; JCR